Restructuring and risk-reduction in mining: employment implications for northern Sweden - Knobblock, Erika Anna; Pettersson, Örjan (Geographical Society of Finland, 2010)
Employment in northern Sweden has in the past been largely dependent on natural resources. Shifting demands and price fluctuations on raw materials has caused boom periods as well as times of crises in local communities. During the first decade of the 21st century, increasing global demand for minerals resulted in substantial investments in the Swedish mining industry. The purpose of this article is to assess the importance of mining for employment in the county of Västerbotten, northern Sweden, by focusing on the time period after 1990. Mining employment constitute merely a small part of all employment in the study area, due to a restructuring process that started in the 1960s. However, results show that mining employment has increased slightly, especially after 2002. Global demand for minerals, related technology and services make it reasonable to believe that this change will have a deeper significance for employment opportunities in the study area Västerbotten. Structural change and restructuring in mining generate new business opportunities in subcontracting, consultancy, equipment production etc, but also new risks. Consequently, it is important to make strategic decisions on how to make use of the development in the local mining industry in order to stimulate long-term regional employment growth.